2001
DOI: 10.1007/s11627-001-0090-2
|View full text |Cite
|
Sign up to set email alerts
|

Thin cell layer culture system in Lilium: Regeneration and transformation perspectives

Abstract: Lilies are one of the most valuable bulbous ornamental cut flower crops and are commercially propagated by conventional scaling, which results in varied bulb quality. This article demonstrates the effectiveness of using specific organ sources in conjunction with the thin cell layer (TCL) system to establish successful organogenic and somatic embryogenic pathways in Lilium longiflorum. TCLs derived from different explant sources, such as receptacle, leaf, young stem, stem node, bulblets, pseudo-bulblets, shoot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…However, in terms of a perennial endangered plant species, a major disadvantage of using (pieces of) bulb scales as explant source is the destruction of the source plant. The lack of an efficient protocol for traditional asexual propagation of lily has prompted extensive studies on using the thin cell layer (TCL) method as both a tool and a solution to the use of bulb scales (Nhut et al 2001a). TCLs have been excised from different plant organs and successfully used as explants for SE and plant regeneration processes in L. longiflorum (Van Le et al 1999;Nhut et al 2001aNhut et al , b, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…However, in terms of a perennial endangered plant species, a major disadvantage of using (pieces of) bulb scales as explant source is the destruction of the source plant. The lack of an efficient protocol for traditional asexual propagation of lily has prompted extensive studies on using the thin cell layer (TCL) method as both a tool and a solution to the use of bulb scales (Nhut et al 2001a). TCLs have been excised from different plant organs and successfully used as explants for SE and plant regeneration processes in L. longiflorum (Van Le et al 1999;Nhut et al 2001aNhut et al , b, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Slow multiplication rate in conventional method is the main constraints in commercial expansion of these species. In vitro micropropagation provides an alternative for the rapid propagation of lilies (Nhut et al, 2001). In recent years, the tissue culture has proven to be most efficient for the mass propagation and multiplication of Lilium genus, as it helps in producing high quality plants (Kanchanapoom et al, 2011), and in maintaining germplasm of endangered and endemic species (Skoric et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of TCL culture is that thin cells layers are similar in physiological terms and can begin all morphogenesis patterns; however, only one pattern can be observed in each treatment (Kiem and Tran, 1981). In addition, direct organogenesis in most plants like Begonia tuberous (Nhut et al 2006), Lilium longiflorum (Nhut et al 2001), Citrus (Carimi et al 1999), Brassica napus (Ghnaya et al 2008) and Digitaria sanguinalis (Le et al 1997) has been reported using TCL. Since morphogenesis from hypocotyls TCL has not been reported in Lycopersicon esculentum Mill, in this research, morphogenesis (callus, shoot, root or somatic embryogenesis induction) containing various concentrations of NAA and two types of cytokinins (BAP and kin) were studied in the hypocotyl TCL of Lycopersicon esculentum Mill seeding.…”
Section: Introductionmentioning
confidence: 99%